Pemigatinib combined with immunotherapy and stereotactic body radiation therapy for FGFR2 fusion-positive advanced intrahepatic cholangiocarcinoma with brain metastasis: a Case Report - Guo, Jiamin; Sun, Lingqi; Chen, Ye; Ma, Ji (Frontiers in Pharmacology, 2024)
Background: FGFR2 fusions or rearrangements occur in 13%-20% of patients with intrahepatic cholangiocarcinoma (iCCA). Pemigatinib, a representative FGFR inhibitor, is commonly used for targeted therapy in such patients. Additionally, brain metastases (BM) are extremely rare in advanced iCCA, and there is currently no standard treatment strategy for advanced iCCA patients with BM. Stereotactic body radiation therapy (SBRT) combined with immune checkpoint inhibitors (ICIs) may exhibit synergistic antitumor effects, presenting a promising approach for advanced iCCA. Case presentation: The patient, a 58-year-old male, experienced a recurrence of iCCA following surgery and chemotherapy, with multiple metastases in the liver, lungs, and brain. Genetic testing revealed FGFR2-TXLNG-fusion, and the patient was treated with pemigatinib in combination with tislelizumab and SBRT for the BM, resulting in significant tumor shrinkage. Adverse events (AEs) such as liver dysfunction, nail loss, and dry mouth were observed during treatment, which were considered to be related to pemigatinib. These AEs were significantly alleviated after dose reduction and symptomatic treatment. Conclusion: This case presented a rare occurrence of FGFR2 fusion-positive iCCA with BM, with extremely limited data on treatment options and survival outcomes in such patients. Our study was the first to report the application of the treatment strategy combining pemigatinib with ICI and SBRT in this specific case. The combined therapy proved effective and well-tolerated, providing new insights for future treatment considerations.